PENGARUH STRUKTUR KEPEMILIKAN DAN KARAKTERISTIK CEO TERHADAP MANAJEMEN LABA RIIL - Wulandari, Wulandari; Susanto, Yulius Kurnia (E-Jurnal Akuntansi TSM, 2024)
The purpose of this study is to obtain empirical evidence regarding the factors that influence real earnings management. The independent variables tested in this study consisted of institutional ownership, managerial ownership, foreign ownership, CEO ownership, CEO tenure, and audit committee activities. While the dependent variable in this study is real earnings management (REM). This study uses manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2021. This income produces a sample of 58 companies with a total of 174 data. The sampling method in this study used a purposive sampling technique and this study used multiple regression analysis. The results of this study show that foreign ownership and CEO ownership have an effect on real earnings management. Meanwhile, institutional ownership, managerial ownership, audit committee activities, and CEO tenure have no effect on real earnings management.